Multiple inducers in aquatic foodwebs: Counter‐measures and vulnerability to exotics. (12th November 2015) - Kerfoot, W. Charles; Savage, Susan C.
Abstract: Do aquatic predator and prey species interact strongly enough to foster specialized coevolutionary feedbacks, or are interactions strongly asymmetrical, with prey species responding much more strongly and to multiple threats? Here we utilize prey induction to measure the strength of interactions around a reciprocal "arms race" candidate ( Epischura ‐ Bosmina ). When prey ( Bosmina ) are transferred from predator‐poor to predator‐rich environments, defensive spines increase in length to achieve a plateau after 12–16 d (1–2 generations). Spine lengths are reversible with predator addition and removal, confirming developmental induction as the major short‐term response. Laboratory assays reveal major geographic variation, implying active evolution. Responses range from almost no spine elongation where Epischura is historically absent (Europe), to major elongation where the predator and prey are in prolonged contact (Laurentian Great Lakes). Trade‐offs (i.e., loss of competitive ability) can be related to spine lengths of the prey species. However, induction is not exclusive to Epischura, as a collection of invertebrate predators also induce spine elongation. Bosmina responses to individual predator species are different, implying active recognition of multiple predation threats in nature. The absence of induction responses to some exotics (e.g., Bythotrephes ) may help explain disproportionate food web impacts. Both revelations underscore the importance of ongoing evolution in aquatic communities.